Collaborative Leadership: A Solution for High Work Intensity Organizations (A Conceptual Review of Organizational Behavior) - Fatima, Arlindo Do Ceo; Andri Yandi (International Journal of Advanced Multidisciplinary, 2023)
Collaborative leadership has become an increasingly relevant approach in modern organizational management, especially in efforts to reduce work-related stress and enhance employee performance. In a high-pressure and complex work environment, this leadership style fosters cooperation, open communication, and active participation from all team members. Through a collaborative approach, leaders can create a more supportive work environment where employees feel heard and valued, thereby minimizing work-related stress. Additionally, by building stronger working relationships and synergy among team members, collaborative leadership has been proven effective in improving both individual and organizational performance overall. This study examines the importance of implementing collaborative leadership as a strategy for managing work-related stress and boosting employee productivity, highlighting various studies and empirical evidence supporting the effectiveness of this approach. The study consists of several parts. First, a literature review focuses on collaborative leadership. Second, the research model and propositions developed in this study are based on a review of previous research literature and discuss in-depth the relationship between work stress and employee performance. The findings of the study indicate that collaborative leadership plays a significant role in reducing work-related stress and enhancing employee performance across various organizations. Collaborative leadership, which emphasizes involvement, participation, and cooperation among team members, has proven effective in creating a more supportive and cooperative work environment, thereby reducing work-related stress and improving employee performance within an organization.